Clinicopathological characteristics of new primary melanomas in patients receiving immune checkpoint inhibitor therapy for metastatic melanoma. (21st February 2022) - Pennington, Thomas E; Zhao, Cathy Yunjia; Colebatch, Andrew J; Fernandez‐Peñas, Pablo; Guitera, Pascale; Burke, Hazel; Scolyer, Richard A; Menzies, Alexander M; Carlino, Matteo S; Lo, Serigne; Long, Georgina V; Saw, Robyn PM
ABSTRACT: Background: Immune checkpoint inhibitors have improved survival in advanced stage melanoma patients. Rates of new primary melanomas (NPM) in patients with prior melanoma have been reported to be as high as 12%. Little is currently known regarding the frequency or characteristics of NPMs occurring in melanoma patients treated with immune checkpoint inhibitors. Aim: To determine the frequency and describe clinicopathologic characteristics of NPMs diagnosed in patients during or after treatment with immune checkpoint inhibitors for metastatic melanoma. Methods: A retrospective analysis of prospectively collected data from the Melanoma Institute Australia and Westmead Hospital Dermatology databases. Clinicopathological data for the initial primary melanoma (IPM) and NPM were compared. Results: Between 2013–2017, 14 NPMs in 13 patients (out of a total of 1047) treated with checkpoint inhibitors were identified. NPMs were significantly thinner than the IPM (median Breslow thickness 0.35 mm vs 2.0 mm, P  = 0.0003), less likely to be ulcerated (0/14 vs 6/13, P  = 0.004) and less likely to have nodal metastases (0/14 vs 6/13, P  = 0.004). NPMs were significantly more likely to be detected in the in‐situ stage (6/14 vs 0/13, P  = 0.0016). Conclusion: NPMs are infrequent in patients treated with checkpoint inhibitors. When they occur, they are usually detected at an early stage and have features associated with a favourable prognosis, most likely reflecting close surveillance. Further study is required to determine long‐term risk in patients achieving a durable response to immune checkpoint inhibitors, and to determine whether the immunotherapy itself influences both their development and biology.